IMPACT OF PERFORMANCE APPRAISAL ON JOB SATISFACTION OF IT EMPLOYEES IN BENGALURU CITY - Lavanya, K.; Rao, Dr. S. Durga (The journal of contemporary issues in business and government, 2023)
This research article aims to “To measure the impact of performance appraisal attributes on the job satisfaction of IT employees”. The paper applies data reduction using Exploratory Factor Analysis (EFA) on a sample of 332 respondents drawn from 6 IT companies in Bengaluru and condenses a set of 19 performance appraisal items converted into a six attributes. A model of how performance appraisal attributes affect adoption is proposed in this study. The present study proposes a model of the impact of various performance appraisal attributes on the job satisfaction. The present study proposes a model of the impact of various performance appraisal attributes on the job satisfaction. The study found that communication & co-operation, evaluation, relatedness, easiness, objectivity and growth & rewards are impacting significantly the job satisfaction. Therefore, managers of IT companies should focus on the above factors to improve job satisfaction of employees. The study investigated the impact of performance appraisal attributes on the job satisfaction. Multiple linear regression analysis highlights that communication & co-operation, evaluation, relatedness, easiness, objectivity and growth & rewards have significant impact on job satisfaction of IT employees.